The Effect of Change Management on Organizational Adaptability in The Age of Technology - Dr. Slamet Riyadi; Helmita; Chevy Herli Sumerli A; Yudhi Anggoro (PT. Anagata Sembagi Education, 2024)
This study aims to investigate the influence of change management on organizational adaptability in the technological era. Using quantitative methods and data collection methods using questionnaires involving 110 respondents from various organizations, the results of the analysis show that change management has a significant influence on organizational adaptability. This shows that an organization's ability to manage change, including readiness to face change and a supportive organizational structure, contributes significantly to improving adaptability. By developing a strategy that includes training, an adaptive culture, and cross-functional collaboration, organizations will be better prepared for a complex and fast-changing environment. These findings provide important insights into the role of change management in creating a responsive work environment and open up opportunities for further exploration of factors that can improve organizational adaptability. towards social responsibility and sustainability, contributing to broader economic growth and a better society.